Advanced cardiac magnetic resonance imaging for assessment of obstructive coronary artery disease—ADVOCATE-CMR study rationale and design - Sonia Borodzicz-Jazdzyk; Geoffrey W. de Mooij; Alexander W. den Hartog; Mark B.M. Hofman; Marco J.W. Götte (Journal of Cardiovascular Magnetic Resonance)
Background: First-pass stress-perfusion cardiovascular magnetic resonance (CMR) imaging is the guidelines-recommended non-invasive test for the detection of obstructive coronary artery disease (CAD). Recently developed quantitative perfusion CMR (QP CMR) allows quantification of myocardial blood flow. Moreover, the latest developments established several methods of CAD assessment without the need for a contrast agent, including stress T1 mapping reactivity (∆T1) and oxygenation-sensitive CMR (OS-CMR). These methods might eliminate the need for contrast administration in clinical practice, reducing time, invasiveness, and costs, thereby simplifying the evaluation of patients with suspected obstructive CAD. The ADVOCATE-CMR study aims to validate QP CMR, ∆T1, and OS-CMR imaging against invasive fractional flow reserve (FFR) for the detection of obstructive CAD. The study also aims to head-to-head compare the diagnostic accuracy of these CMR techniques with the conventional visual assessment of stress-perfusion CMR and to correlate them to short- and long-term clinical outcomes. Study design and Methodology: ADVOCATE-CMR is a single-center, observational, prospective, cross-sectional cohort study. The study will enroll 182 symptomatic patients with suspected obstructive CAD scheduled for invasive coronary angiography (ICA). Before ICA, all participants will undergo CMR imaging, including OS-CMR with breathing maneuvers, rest, and adenosine stress T1 mapping and rest and adenosine stress first-pass perfusion. Subsequently, ICA will be performed, including FFR, instantaneous wave-free ratio, resting Pd/Pa, coronary flow reserve, and index of microvascular resistance measurements in all main coronary arteries. A follow-up CMR scan with the same protocol will be performed at 3 months after ICA. Clinical follow-up will be performed at 3, 6 months, 1 and 3 years after ICA. Conclusion: The ADVOCATE-CMR will be the first study comprehensively evaluating and comparing head-to-head the diagnostic performance of a range of contrast- and non-contrast agent-based CMR imaging methods (including QP CMR, ∆T1, and OS-CMR) for the detection of FFR-defined obstructive CAD. We expect to establish a validated and time-efficient diagnostic workflow available to a wide range of general CMR services. Finally, these improvements may enable CMR to become an effective non-invasive, radiation-free gatekeeper for ICA in patients with suspected obstructive CAD, potentially without the need for a contrast agent.